Applications of Multi-reduction and Multi-soliton Analysis of (2+1) Zakharov-Kuznetsov (ZK) Equation - Ali Raza; Abdul Hamid Kara; Sibusiso Moyo (East European Journal of Physics)
We study the Zakharov-Kuznetsov (ZK) equation with the triple-power law non-linearity. We determine the invariance properties and construct classes of conservation laws and show how the relationship leads to double reductions of the systems, yielding stable solutions such as travelling waves and solitons. This relationship is determined by recent results involving ‘multipliers’ that lead to ‘total divergent systems’. Multi-solitons analysis is performed using invariance transformation, producing stable multi-soliton structures, alongside vortex soliton solutions that exhibit localized, bell-shaped profiles. A comparison between symmetry and multi-reduction is presented, highlighting the efficacy in achieving integrable outcomes. The physical interpretation of soliton solutions is also discussed in this study, emphasizing their stable propagation and relevance to modeling coherent ion-acoustic and vortex waves in magnetized plasmas.